Patients' Experiences of Emergency Hospital Care Following Self-Harm: Systematic Review and Thematic Synthesis of Qualitative Research. (February 2020) - MacDonald, Sarah; Sampson, Catherine; Turley, Ruth; Biddle, Lucy; Ring, Nicola; Begley, Roisin; Evans, Rhiannon
Rates of hospital presentation for self-harm have increased in recent years, and although clinical practice guidelines on clinical provision prioritize positive patient experiences, the quality of provision remains variable. This systematic review provides an updated and extended synthesis of qualitative research on the following: (a) patients' experiences of treatment following presentation to hospital; and (b) patients' perceptions of the impact of treatment on recurrent self-harm and/or suicidal ideation, and future help-seeking. Twenty-six studies were identified for inclusion in the final synthesis. Three meta-themes emerged: (a) individuals undertake extensive identity work when presenting with self-harm, navigating the process of becoming a patient, and negotiating the type of patient they want to be; (b) care ranges from gentle to hostile, with care at admission and discharge being particularly disorientating; and (c) negative experiences of clinical treatment may increase future self-harm. Emerging research gaps include the need for further theoretically informed qualitative research in this area.